2021
DOI: 10.33073/pjm-2021-026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Enzymes Producing Bacterial Endophytes of Some Poaceae Plants

Abstract: Endophytic bacteria represent microorganisms that live during the whole life cycle within the tissues of healthy plants without causing any obvious signs of disease. In this study, the ability of 128 endophyte bacterial isolates from some cultivated and wild grain plants (Poaceae family) in Van, Turkey, were investigated in terms of producing several extracellular hydrolytic enzymes. It was demonstrated that lipases, proteases, amylases, cellulases, pectinases, and xylanases were produced by the bacteria with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Treatment of rats with MTX In our study TNF Alfa was significantly increased in MTX intoxicated rats which is evidenced by [35][36][37] who all showed that MTX induced hepatotoxicity is accompanied by increment in TNF-Alpha level.MK showed significant reduction in the level of TNF in hepatic tissue which was also documented by many other studies [28][29] who found that Montelukast treatment reduced TNF level in hepatic tissue during ischemia reperfusion injury and Endotoxaemia respectively [30] who found that Montelukast reduced TNF level in gut tissue by its antinflammatory effects.…”
Section: Effect Of Methotrexate and Montelukast On Inflammatory Param...supporting
confidence: 75%
See 1 more Smart Citation
“…Treatment of rats with MTX In our study TNF Alfa was significantly increased in MTX intoxicated rats which is evidenced by [35][36][37] who all showed that MTX induced hepatotoxicity is accompanied by increment in TNF-Alpha level.MK showed significant reduction in the level of TNF in hepatic tissue which was also documented by many other studies [28][29] who found that Montelukast treatment reduced TNF level in hepatic tissue during ischemia reperfusion injury and Endotoxaemia respectively [30] who found that Montelukast reduced TNF level in gut tissue by its antinflammatory effects.…”
Section: Effect Of Methotrexate and Montelukast On Inflammatory Param...supporting
confidence: 75%
“…Following this, blood samples were drawn directly from the left ventricle of the heart via a cardiac puncture. Blood samples were then placed in tubes containing clot activator gel and allowed to coagulate at 37C before being centrifuged at 3000 rpm for 10 minutes to extract the serum [21]. The subsequent serum collected is used to determine the levels of total serum bilirubin (TSB), alkaline phosphatase (ALP), aspartate aminotransferase (AST), and alanine aminotransferase (ALT).…”
Section: Procedures Blood Sample Preparationmentioning
confidence: 99%
“…In this study, most of the isolates showed at least one extracellular enzyme production activity including cellulase, pectinase and amylase. Hydrolytic enzymes like cellulase, pectinase and amylase might play important role in endophytic colonization and establishment of bacteria in plant tissues ( Dogan and Taskin, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it appears that these hydrolytic enzymes could be responsible for the remarkable inhibition of F. graminearum . Here, it is worth mentioning that with the help of these extracellular hydrolytic enzymes, endophytes can penetrate the plant tissue and play a vital role in endophytic colonization and establishment inside the host plant [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%